Teori Belajar Sosial Kognitif Albert Bandura dalam Pembelajaran Pendidikan Agama Islam - Dian Nupus; Hasbiyallah; Tarsono (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
Abstract. This study aims to examine Albert Bandura's cognitive social learning theory and its implementation in learning Islamic religious education. This research method is a qualitative research using descriptive analysis in the form of library research. Data is collected through analysis of accredited books and journals that are relevant to the problem. The data analysis technique used is the Miles and Huberman data analysis technique which consists of data reduction, data presentation and conclusion drawing. At the data reduction stage, the author will sort out the data in accordance with the research study which is then presented through words to produce new findings. Then the author formulates conclusions as verification of research findings. Based on the research results, it is found that Albert Bandura's social cognitive learning theory is relevant to Islamic religious education learning. This can be seen from Albert Bandura's cognitive social learning theory can be used in Islamic religious education, Albert Bandura's cognitive social learning theory is in line with the exemplary and habituation methods taught by Islam, and the process of observational learning and modeling which requires repetition in its application is also used in Islamic religious education learning.